Sustainabillity Ratio pada Bank Umum Syariah di Indonesia Beserta Faktor yang Mempengaruhinya - Dirvi Surya Abbas; Arry Eksandy; Yuniarti Yuniarti (Universitas Islam Lamongan, 2020)
The purpose of this study are to determine the effect of Capital Adequacy Ratio (CAR), Operational Cost of Operating Income (BOPO), Financing Deposit Ratio (FDR) on financial sustainability ratio (FSR) (Empirical Study on Islamic Banking in Indonesia in 2014 - 2018). The research period time used was 4 years, namely the 2014-2015 period. The population of this study includes all Islamic general banking in Indonesia in the 2014-2015 period. The sampling technique was using a purposive sampling technique. Based on the predetermined criteria, 8 companies were obtained. The type of data used is secondary data obtained by financial reports issued by the bank. The analysis method used is panel data regression analysis. The results show that the Capital Adequacy Ratio (CAR) has a significant positive effect on financial sustainability ratio (FSR). Operational Cost Operating Income (BOPO) doesn’t have effect on financial sustainability ratio (FSR). Financing Deposit Ratio (FDR) doesn’t have effect on financial sustainability ratio (FSR). Keywords: financial sustainability ratio (FSR); capital adequacy ratio (CAR); operational cost of operating income (BOPO); financing deposit ratio (FDR)